2019
DOI: 10.12973/eu-jer.8.2.617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Empowerment on Teachers’ Organizational Behaviors

Abstract: This descriptive and regression research was conducted to determine the influence of empowerment on organizational behaviors of 215 teachers in Catholic Higher Education Institutions in the Philippines. The results revealed that Catholic teachers have high levels of teacher empowerment. Specifically, they have very high level of status, professional growth, self-efficacy, and impact and high level of decision-making and autonomy in scheduling. Meanwhile, they also high level of organizational behaviors. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 76 publications
5
26
0
1
Order By: Relevance
“…In addition, more than a half of teachers reported improvement in self -efficacy, status, and problem solving ability. The study findings are consistent with the findings in a study by Tindowen (2019), which revealed that empowered teachers had high level of self-efficacy and professional growth. They have ability and power to handle various situations and overcome challenges.…”
Section: Teachers Empowermentsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, more than a half of teachers reported improvement in self -efficacy, status, and problem solving ability. The study findings are consistent with the findings in a study by Tindowen (2019), which revealed that empowered teachers had high level of self-efficacy and professional growth. They have ability and power to handle various situations and overcome challenges.…”
Section: Teachers Empowermentsupporting
confidence: 91%
“…Not only are empowered teachers in charge of their own development, but they are also powerful agents of change. Their knowledge and competencies are important in restructuring education process (Tindowen, 2019;Braga, Jones, Bulger & Elliot, 2016). UNESCO (2017) shows that there are competencies that enable an individual to be proactive, self-organised, and focused in different contexts and situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the years, human resources are considered as the most important assets in any organization. Human resources are the moving force of an organization and harnessing their capabilities will contribute much in bringing about quality and productivity (Tindowen, 2019;Wright & McMahan, 2011;Ployhart & Molterno, 2011). Because persons are vital in organizations, it is then necessary that top level management should treat them as the utmost priority.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' self-efficacy beliefs have impact on teachers' goals, the efforts they invest in teaching, and their persistence when they face obstacles (Rimm-Kaufman & Hamre, 2010;Tschannen-Moran et al, 1998). Tindowen (2019) found that teachers' self-efficacy predicts organizational behaviours which include affective organizational commitment, continuance organizational commitment, normative organizational commitment, supervisory support, job involvement, organizational citizenship behaviour, teacher professionalism commitment, and professional commitment to teaching work.…”
Section: Teachers' Sense Of Self-efficacymentioning
confidence: 99%